2019
DOI: 10.3390/ijerph16193621
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Level Path Analysis of the Relationships between the Momentary Experience Characteristics, Satisfaction with Urban Public Spaces, and Momentary- and Long-Term Subjective Wellbeing

Abstract: Previous research has shown that the urban environment could influence people’s behavior and wellbeing. However, little is still known about how the objective and subjective measures of the momentary experience of urban public spaces could contribute to the satisfaction with the urban environment of cities, which eventually could influence the momentary and long-term subjective wellbeing (SWB) of citizens. Therefore, the aim of this research is to gain insight into how momentary experience and satisfaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 75 publications
4
29
0
Order By: Relevance
“…Ettema and Smajic [41] show that walking alone leads to negative affective state compared to walking in company. However, Weijs-Perrée et al [43] found that having a travel company has no influence on the immediate experiences.…”
Section: Visitor Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ettema and Smajic [41] show that walking alone leads to negative affective state compared to walking in company. However, Weijs-Perrée et al [43] found that having a travel company has no influence on the immediate experiences.…”
Section: Visitor Characteristicsmentioning
confidence: 99%
“…Although above mentioned theories from studies such as Hull [12], Csikszentmihalyi and Hunter [10], Eid and Diener [36] and Mannell and Iso-Ahola [32] are relevant to event experiences, they disregard the influence of physical environment characteristics. In addition, urban planning related studies such as Kevin Lynch [44], Birenboim [40], Ettema and Smajic [41] and Weijs-Perrée et al [43] discuss the immediate experiences in the built environment but not specifically during large-scale events. However, generic experiences and event experiences may differ as visitors probably have some expectations of event experiences while generic experiences can occur anywhere or anytime.…”
Section: Contextual Characteristicsmentioning
confidence: 99%
“…The concept of affordances highlights several interrelated qualities of environments [ 24 ] and the action-oriented aspects of human perceptions [ 25 ]. Spatial affordances for creativity thus relates to peoples’ well-being, since participation and integration in the immediate social environment are important to both mental and physical health [ 8 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we introduce an interdisciplinary methodology, illustrated with a pilot study of the experiences of urban stress among people who work in urban environments to demonstrate the necessity of navigating between scientific and interpretivist modes of analysis to account for the complex relationship between the body, emotions and environment. It is increasingly commonplace to consider the emotional dimensions of urban mobility and transport planning through an attention to the sensory and affective experiences of commuters [20][21][22][23]. The intersection of senses, emotions and subjective wellbeing has shaped an extensive research field on both workplace and commuter wellbeing [24].…”
Section: Introductionmentioning
confidence: 99%
“…'Active' commuting (e.g., by bike, walking) has been found to be less stressful than driving [25,26], longer commutes increase levels of stress [27], and the effects of a long commute impact on people's mood at work [28]. More 'ecological' in situ studies which ask people to map their activity in real time, and rate their mood or positive/negative experiences of public space have also found that physical characteristics of cities such as distance from facilities can shape people's subjective wellbeing as they move through space [18,23]. The appeal of mobile or wearable biosensor technology is that it promises to enhance these understandings through more 'objective' measurement of stress and wellbeing, which can be tracked by GPS in real-time [29] and can be integrated into smart city networks [30].…”
Section: Introductionmentioning
confidence: 99%